Anchoring Single Copper Atoms to Microporous Carbon Spheres as High‐Performance Electrocatalyst for Oxygen Reduction Reaction. (16th July 2021) - Zong, Lingbo; Fan, Kaicai; Wu, Weicui; Cui, Lixiu; Zhang, Lili; Johannessen, Bernt; Qi, Dongchen; Yin, Huajie; Wang, Yun; Liu, Porun; Wang, Lei; Zhao, Huijun
Abstract: Although the carbon‐supported single‐atom (SA) electrocatalysts (SAECs) have emerged as a new form of highly efficient oxygen reduction reaction (ORR) electrocatalysts, the preferable sites of carbon support for anchoring SAs are somewhat elusive. Here, a KOH activation approach is reported to create abundant defects/vacancies on the porous graphitic carbon nanosphere (CNS) with selective adsorption capability toward transition‐metal (TM) ions and innovatively utilize the created defects/vacancies to controllably anchor TM–SAs on the activated CNS via TMN x coordination bonds. The synthesized TM‐based SAECs (TM‐SAs@N‐CNS, TM: Cu, Fe, Co, and Ni) possess superior ORR electrocatalytic activities. The Cu‐SAs@N‐CNS demonstrates excellent ORR and oxygen evolution reaction (OER) bifunctional electrocatalytic activities and is successfully applied as a highly efficient air cathode material for the Zn–air battery. Importantly, it is proposed and validated that the N‐terminated vacancies on graphitic carbons are the preferable sites to anchor Cu‐SAs via a Cu(NC2 )3 (NC) coordination configuration with an excellent promotional effect toward ORR. This synthetic approach exemplifies the expediency of suitable defects/vacancies creation for the fabrication of high‐performance TM‐based SAECs, which can be implemented for the synthesis of other carbon‐supported SAECs. Abstract : A KOH activation approach is used to create abundant vacancies on the porous graphitic carbon nanospheres, and the created vacancies are utilized to controllably anchor transition‐metal single atoms (TM‐SAs, TM: Cu, Fe, Co, and Ni) via a TM(NC2 )3 (NC) coordination configuration with superb oxygen reduction reaction activity. The exemplified approach is applicable to fabricate high‐performance TM‐SA electrocatalysts.